Des camps de réfugiés espagnols de la guerre civile dans l’Hérault - Vincent Parello (Mélanges de la Casa de Velázquez, 2011)
This article uses unpublished documents in the Archives of the Department of Hérault to examine the policy of administrative internment of Spanish refugees implemented by the Prefect Antoine Monis throughout 1939. There were four types of camp in Hérault : the «concentration camp» at Agde, the «holding camps» at Sète, Lodève, Clermont-l’Hérault and Ceilhes-et-Rocozels, the «sorting camp» at Villodève in Montpellier, and the «specialised camps» at Béziers, Pézenas and Saint-Bauzille-de-Putois.